The Delegation of State Sovereignty over Air Space in the Implementation of Air Navigation: The Analysis of the Agreement between Indonesia and Singapore on Management of the Batam and Natuna Flight Information Region - Endang Puji Lestari (Universitas Lampung, 2017)
The state sovereignty over airspace with its complete and exclusive nature experiences a significant dynamic in both its concept and implementation in the international air law. Sovereignty over the airspace not only provides legislative, executive, and judicialauthorities of the state but also puts an obligation on the state to provide facilities for aviation safety. The reason for aviation safety airspace of a sovereign state can be delegated to other states to manage the service of navigation, for example, Indonesian air spaces in the Natuna and Batam, are maintained by Singapore for the sake of aviation safety. The taking over of the management of FIR in Batam and Natuna had been carried out through several steps. First, establishing Civil Military Aviation Coordination (CMAC) as outlined in the Government Regulation (Ministry of Transportation Regulation Number 55 on 2016) concerning the order of the national airspace. Second, evaluating the implementation of air navigation by reformulating the institutional of LPPNPI, evaluating the cooperation agreement between the Government of Indonesia and Singapore, and providing air navigation service during the transition period in Natuna Islands. Third, conducting the taking over concept phase by phase, in which the first phase, Singapore only provides air navigation service, while Indonesia only monitors. The second phase, Indonesia provides air navigation services, while Singapore only monitors, and for the third phase, as the final implementation, Indonesia provides air navigation services fully. Keywords: Delegation, Sovereignty, Air Space, Air Navigation, Agreement